Target Mathematics for GCSE - Roebuck, E.; Sherlock, A.; Godfrey, M.; Pickles, J. (Delhi : Bombay : Calcutta : Oxford University Press, 1992)
This maths programme offers a two-year course for Key Stage 4/GCSE students expected to reach Level 6 or 7. It includes opportunities for teacher/class discussion, many tasks, exercises and puzzles, and sections for practice and the review of previous work.
Include index.
Keywords: Mathematics -- Study and teaching